Pas members fear Azizan is a liability - News Straits, Times (New Straits Times, 2013)
BOGEYMAN is not a familiar term used in local politics. For Pas however, the term whose Malay equivalent would be "kambing hitam", is fast being used to explain all that has gone wrong in Kedah.